EATS study : eating attributes of tertiary students and potential influencing factors on diet quality : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Nutrition and Dietetics at Massey University, Auckland, New Zealand - Panossian, Armand (Massey University, 2019)
Background: In order to improve diet quality, it is important to assess its potential determinants. Literature indicates young adults attending university engage in unhealthy behaviour and may be at risk of establishing undesirable dietary habits that continue into later adulthood. An understanding of the dietary patterns and associated factors in this population is needed, particularly in New Zealand where the literature is sparse. Aims: To investigate diet quality and potential influencing factors in a group of university in New Zealand. Methods: Diet quality and associated factors were measured in a pilot sample of university students enrolled at Massey University’s Albany Campus, Auckland, New Zealand. A self- administered online questionnaire was used to collect data on dietary habits as well as factors that have been associated with diet quality in previous research. A Diet index was developed and scored against the dietary recommendations outlined in the Eating and Activity Guidelines for New Zealand Adults. Results: Forty university students were recruited in the study. The overall mean diet quality score was 54.2 (±10.6) points out of 80. The majority of participants met dietary guidelines for fruit (70%), vegetable (57.5%) and ‘Extra’ food intake (77.5%), while less than half of participants met dietary guidelines for grains (2.5%), wholegrains (30%), alcohol (40%), saturated fat (32.5%), added sugar (25%) and added salt (10%). Of the potential influencing factors investigated, healthy eating attitudes (P=<0.01), binge drinking and use of dietary supplements (P=≤0.04), food preparation (P=<0.01), as well as confidence in basic cooking techniques (P=0.05) were significantly associated with diet quality. Conclusions: The current study identified potential influencing factors as well as components of the diet in this population that were below dietary recommendations, and findings suggest university students show clustering of health-related behaviours. This is particularly concerning given the evidence that university students lack the confidence and/or ability to prepare meals that contribute to optimal dietary habits, and are likely to engage in binge drinking; which was negatively associated with diet quality in the current study. Further research with improved methodology, specifically in regards to the diet quality index used, is needed to build on the findings in this study.
Keywords: College students; Nutrition; New Zealand; Auckland; Attitudes; 321002 Food properties (incl. characteristics and health benefits)